Generalizing the Presuppositional Approach to the Binding Conditions. (1st September 2021) - Bruening, Benjamin
Abstract: Almost all current approaches to the binding theory (the conditions that regulate covaluation between NPs within a sentence) have accepted the view that the binding theory should regulate only syntactic binding and not coreference. In this article, I argue that this is incorrect and that we need a binding theory that regulates both binding and coreference, as the classical binding theory had it. I also show some problems with the idea that the binding conditions somehow involve or should reduce to syntactic movement or syntactic agreement (Agree), as many recent works argue. I suggest instead that we should pursue a presuppositional approach to the binding conditions, as has been proposed for Binding Condition A. I spell out such an analysis and illustrate some benefits of pursuing it.